(Re)thinking children’s picturebooks as the mirror of contemporary society - Ellinor Skaremyr; Carina Hermansson; Getahun Yacob Abraham; Margareta Lindström (Journal of Early Childhood Education Research, 2024)
This study deals with all children’s possibilities of meeting the multilingual society and aims to explore the norms regarding language and culture that are reflected in picturebooks in preschools. Previous research has shown how picturebooks can be used to develop literacy skills and intercultural understandings among children. A postcolonial lens is used to identify social locations and thereby unfold hidden power relations and social positionings of who is to be included and who is not (Spivak, 1988; Yuval-Davis, 2006). 35 picturebooks collected from preschools in Iceland, Norway and Sweden have been analysed by frequency and qualitative content analysis, eleven of which were found to contain multilingualism and/or multiculturalism. The results show a) a prevailing monolingual norm in which solely artefacts carry multilingual trails; b) a strong monocultural norm, which places people of diversity in a marginalised position; c) the English language holds an advanced position compared to majority languages, which situates other minority languages as anomalous. The educational significance of the research implicates a need for multilingual and multicultural diversity to be more observable in picturebooks used in preschool, to help children develop languages, and their own linguistic and cultural identity/-ies and, thus, their sense of belonging to a multilingual society.